2010
DOI: 10.1007/s00068-010-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic limb amputations at a level I trauma center

Abstract: Traumatic limb amputation is a rare consequence of civilian trauma. Amputation is rarely the primary cause of death; however, these devastating injuries are associated with significant intensive care unit and hospital lengths of stay. Although no mortality difference was detected, when compared with patients with upper extremity amputations, patients with lower extremity amputations were more severely injured, required revision extremity surgery more often, had a higher complication rate, and more frequently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
8
4
Order By: Relevance
“…The majority of amputations in Iran were occupational injuries whereas non-occupational injury accounted for the majority of the cases we studied. The differences in the anatomical distribution of amputation between this study and that of Nasser et al could be explained by the findings reported by Kobayashi et al [8] and Lang et al [9]. Kobayashi et al, in a similar study in California, observed that the lower extremity amputation was more likely when the causative factor was road traffic accidents, whereas the upper extremity amputation was more likely in work-related accidents [8].…”
Section: Discussioncontrasting
confidence: 49%
“…The majority of amputations in Iran were occupational injuries whereas non-occupational injury accounted for the majority of the cases we studied. The differences in the anatomical distribution of amputation between this study and that of Nasser et al could be explained by the findings reported by Kobayashi et al [8] and Lang et al [9]. Kobayashi et al, in a similar study in California, observed that the lower extremity amputation was more likely when the causative factor was road traffic accidents, whereas the upper extremity amputation was more likely in work-related accidents [8].…”
Section: Discussioncontrasting
confidence: 49%
“…There is a significant difference in kinetic energy between improvised explosive devices (IEDs) blasts and road traffic collisions (RTC); therefore, the severity and characteristics of these injuries are different. In contrast with previous studies [5,[11][12][13], our results show that the most common mechanism of LLA in the civilian population was subway train run-over with 9 (26.4%) patients, and pedestrian run-over, with 8 (23.6%) patients. These results are consistent with the data from the National Trauma Databank [12].…”
Section: Limitations Of the Studycontrasting
confidence: 99%
“…Consequently, those last three patients had more complications, more operative procedures, and longer hospital LOS than those patients treated with urgent amputation, as is usually the case [14]. Regarding these postoperative complications, the majority of them were related to wound infection, (grade III of the Clavien-Dindo classification), also reported by other studies [5]. Management of these complications required a multidisciplinary approach with participation of plastic, orthopedic, and vascular surgeons.…”
Section: Limitations Of the Studymentioning
confidence: 74%
See 2 more Smart Citations